„Bibliotekarz” 1919-1929-1939 – czasopismo fachowe nie tylko dla bibliotekarzy. Cz. I: geneza, założenia, cechy formalne (Heteroglossia – studia kulturoznawczo-filologiczne, 2021)
In the years 1919, 1929-1939, the Polish Librarians’ Association together with the Public Library of the Capital City of Warsaw published a professional and popular periodical under the titles: „Bibliotekarz” and „Bulletin of the Public Library of the Capital City of Warsaw”. In he text presents the origins of the magazine, difficult beginnings (1919), then an uninterrupted 10-year history (1929-1939). The formal features of the magazine (circulation, format, frequency, volume, price) were discussed in detail. In the full chronological perspective, covering 11 years, the transformations of writing, its profile, internal composition, composition, including the most important sections, are shown. The content of the magazine was analyzed, which made it possible to characterize the texts in terms of subject, geographical and personal range. Although oriented towards librarians, the ’librarian’ had ambitions to reach other circles as well, or at least draw librarians’ attention to the various fields of knowledge represented in the library. This is evidenced by bibliographic lists of books from various scientific disciplines. „The Librarian” (1919, 1929-1939), as convinced by the detailed analysis carried out, is still today a valuable source of information about Polish librarianship in the interwar period.